2021
DOI: 10.3389/fphar.2021.675003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiarrhythmic Drugs on hERG Gating in Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes From a Patient With Short QT Syndrome Type 1

Abstract: Aims: The short QT syndrome type 1 (SQT1) is linked to hERG channel mutations (e.g., N588K). Drug effects on hERG channel gating kinetics in SQT1-cells have not been investigated.Methods: This study used hiPSC-CMs of a healthy donor and a SQT1-patient carrying the N588K mutation and patch clamp to examine the drug effects on hERG channel gating kinetics.Results: Ajmaline, amiodarone, ivabradine, flecainide, quinidine, mexiletine and ranolazine inhibited the hERG channel current (IKr) less strongly in hiPSC-CMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Direct comparisons should, therefore, be made with caution, ideally between groups studied under identical conditions. Nevertheless, similar to previous studies, our hiPSC-CM show a relatively immature phenotype characterized by less negative RMP, slower AP upstroke velocity and automaticity [ 8 , 18 , 26 ]. Lack of I K 1 is a hallmark of hiPSC-CM [ 23 , 50 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Direct comparisons should, therefore, be made with caution, ideally between groups studied under identical conditions. Nevertheless, similar to previous studies, our hiPSC-CM show a relatively immature phenotype characterized by less negative RMP, slower AP upstroke velocity and automaticity [ 8 , 18 , 26 ]. Lack of I K 1 is a hallmark of hiPSC-CM [ 23 , 50 ].…”
Section: Discussionsupporting
confidence: 88%
“…Bath solution contained (in mmol/L): CsCl 144, CaCl 2 2, MgCl 2 2, glucose 5, HEPES 10 (pH = 7.4 adjusted with CsOH). Pipette solution contained (in mmol/L) CsCl 20, EGTA 10, HEPES 10, CsF 110 (pH = 7.2 adjusted with CsOH) in accordance with a recently published protocol [ 26 ]. Cs + was used as a charge carrier due to its selectivity for the hERG channel [ 65 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these drugs may be potential candidates for treating or preventing ventricular tachyarrhythmias in individuals with SQTS1 carrying the KCNH2 –N588K variant. 6 , 7 Other studies have shown that quinidine, disopyramide, 42 , 43 , 44 vernakalant, 45 but not sotalol, could prolong APD or suppress arrhythmia in hiPSC-CMs from an SQTS1-patient carrying KCNH2 –N588K. These findings suggest that KCNH2 –N588K may have different effects on drug responses, which could help explain why SQTS patients with KCNH2 –N588K have varying responses to hERG channel blockers.…”
Section: Short Qt Syndromementioning
confidence: 92%
“… 5 This variant has been shown to render the hERG channel resistant to some drugs. 4 , 6 , 7 Additionally, other gene variants have been reported to impact drug efficacy in patients with genetic arrhythmias. This review will summarise the reported data on drug effects from studies conducted in patients and experimental models of LQTS and SQTS with different gene variants, and will discuss the possible mechanisms through which gene variants affect drug efficacy (see Fig.…”
Section: Introductionmentioning
confidence: 99%